R E V I E W: Species Diversity of Local Fruit Trees in Kalimantan: Problems of Conservation and Its Development - MUSTAID SIREGAR (Society for Indonesian Biodiversity, 2006)
The decrease in population of local fruit trees due to the forest destruction in some places in Kalimantan is a worrying trend.The genetic diversity of fruits in Kalimantan has been saved partly through indigenous agroforestry, as species cultivated from generation to generation by indigenous people have created miniature forests in the village agroecosystem. However, there is no doubt that the existence of local fruit trees has been threatened by the introduction of a superior fruit cultivars and other commercial plant species such as coconuts (Cocos nucifera), oil palm (Elaeis guinensis) and rubber trees (Hevea braziliensis). An ex-situ conservation program is proposed for the maintenance of diversity amongst local fruit species. Â© 2006 Jurusan Biologi FMIPA UNS Surakarta Key words: Local fruit trees, indigenous agroforestry, conservation, Kalimantan.